Public Knowledge and Trust of Agricultural and Natural Resources Organizations - Quisto Settle; Joy N. Rumble; Keelee McCarty; Taylor K. Ruth (Journal of Applied Communications, 2017)
The public lacks knowledge and connectedness to agriculture and natural resources in the United States, leading to a need for effective communications from agricultural and natural resources organizations. Trust is an integral component of communications, but it is not well understood how the public trusts the various organizations communicating agricultural and natural resources issues. The study evaluated non-profit, for-profit, and governmental organizations. A survey was conducted of a representative sample of the U.S. population to assess the public’s awareness, knowledge, and trust of organizations and their communications. The highest number of respondents was aware and knowledgeable of governmental organizations, except for Extension. Communications from non-profit organizations tended to be trusted the most compared to for-profit organizations and governmental organizations, except for Extension. Respondents’ trust of the non-profit organizations was typically higher than for-profit organizations and governmental organizations, except for Extension. The relationship between trust of an organization and trust of its communications were statistically significant for all organizations, while relationships between trust of an organization and knowledge of an organization were typically negligible and not statistically significant. For-profit organizations and governmental organizations should work to improve the public’s trust. Extension should seek to improve the public’s awareness and knowledge given the level of trust the knowledgeable respondents had for the organization. Future research should address what factors are influencing the public’s trust in organizations and organizations’ communications.
Keywords: Agriculture; Communications; Natural Resources; Organizations; Trust